Exploring the potentiality of Mandla's distinct landlocked aquatic food systems typology: A case study - Samaddar, Ayan; Shijagurumayum, Meghajit; Krishnan, Smitha; Mandal, Nirmallya; Malaiappan, Sudharsan; Borah, Gulshan; Panemangalore, Arun Padiyar; Kumar, Gopal (2024)
Malnutrition is a serious issue in Madhya Pradesh since the state has one of the highest rates of undernutrition in India. Here, some of the main threats to people's health and nutritional security are dietary deficiencies in iron, calcium, zinc, protein, and vitamin A. In Mandla, these problems are likewise at an alarming stage. This district is regarded as one of the least economically developed area in India and relies mostly on a variety of rainfed agricultural and forest goods for its livelihood and household nourishment. Aquatic foods (especially animal-based), might be a helpful way to address challenges related to economic development and malnutrition. The increasing fish production and shifting dietary preferences within the community, particularly the inclusion of non-vegetarian food items, indicate a favorable opportunity to enhance the aquatic food system in Madhya Pradesh. Hence, comprehending the aquatic food systems rooted in the diverse water resources of Mandla, a distinctive landlocked region, could unveil a novel and previously underexplored avenue for development.